PUBLIC SERVICE PERFORMANCE OF BLOOD TRANSFUSION UNITS DR SOEKARDJO REGIONAL GENERAL HOSPITAL - Mohamad Fanji Ferdiansyah; Fachmi Syam Arifin; Budi Setiadi (JGSRD: Journal of Government Science and Rural Development, 2022)
The background of this research is that there has been no performance appraisal of the Blood Transfusion Unit of RSUD dr Soekardjo for almost 6 years of operation. This study aims to explain the performance of public services carried out by the Blood Transfusion Unit of RSUD dr Soekardjo. This research method is qualitative. Informants in this study found 6 people consisting of the head of the room and 5 people in charge of implementing it. Data collection techniques are by conducting interviews, observation, and documentation. The analysis technique used is the descriptive data analysis technique. After collecting data and recording data, the researcher performs data processing or analysis consisting of data reduction, data presentation, and reports. Results Based on the research that the performance of the Blood Transfusion Unit of RSUD is still not optimal. This is indicated by the productivity of employees who are still lacking in socializing blood donors and planning and preserving blood donors. The second is related to where employees still need to improve their ability to maintain facilities in order to provide comfort to service users and are often late so that services are hampered. The third is related to responsiveness where employees are still lacking in providing innovative services so that they are still unable to compete with other parties but in responding to complaints and community needs are sufficient. The fourth relates to the responsibilities carried out by employees who are quite good because employees are always emphasized to provide services according to SOPs and are alert if there are donors who feel dizzy, nauseated, and swollen and are responsible until the donor recovers. Finally, regarding employee accountability, there are still shortcomings where employees are still not able to carry out services by the vision and mission of the Blood Transfusion Unit of RSUD. In terms of service, it is quite good. Employees are also transparent about the cost of blood processing. Finally, regarding employee accountability, there are still shortcomings where employees are still not able to carry out services by the vision and mission of the Blood Transfusion Unit of RSUD. In terms of service, it is quite good. Employees are also transparent about the cost of blood processing. Finally, regarding employee accountability, there are still shortcomings where employees are still not able to carry out services by the vision and mission of the Blood Transfusion Unit of RSUD. In terms of service, it is quite good. Employees are also transparent about the cost of blood processing.